A constraint-based language for modelling intelligent environments - Gallardo, María-del-Mar; Lavado, Leticia; Panizo, Laura; Titolo, Laura (Journal of reliable intelligent environments, 2017)
Intelligent environments can be described as hybrid systems, which combine continuous dynamics, modelling the behaviour of physical components, and discrete dynamics, modelling the software components that control the evolution of the physical variables. The growing boom in intelligent environments makes the construction of complex discrete components necessary, which may require the use of more sophisticated concurrent languages. H y- tccp is a concurrent language for modelling hybrid systems with high-level notations that facilitate the description of computational systems, abstracting away from the implementation details. In this paper, we present an operational semantics based on hybrid automata for H y- tccp which is a theoretical basis for the analysis and verification of hybrid systems like intelligent environment.